2022
DOI: 10.3389/fgene.2022.937300
|View full text |Cite
|
Sign up to set email alerts
|

A transmembrane protein family gene signature for overall survival prediction in osteosarcoma

Abstract: The transmembrane (TMEM) protein family is constituted by a large number of proteins that span the lipid bilayer. Dysregulation of TMEM protein genes widely occurs and is associated with clinical outcomes of patients with multiple tumors. Nonetheless, the significance of TMEM genes in the prognosis prediction of patients with osteosarcoma remains largely unclear. Here, we comprehensively analyzed TMEM protein family genes in osteosarcoma using public resources and bioinformatics methods. Prognosis-related TMEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Based on the current study showing a signi cant increase in TMEM147 expression in colon cancer, it may be substantially involved in the pathogenesis of colon cancer [19]. In osteosarcoma, TMEM147 expression was negatively correlated with patient prognosis [20]. Several studies have shown that the function of the endoplasmic reticulum is closely related to hepatocellular carcinoma, but TMEM147 has not been reported in hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Based on the current study showing a signi cant increase in TMEM147 expression in colon cancer, it may be substantially involved in the pathogenesis of colon cancer [19]. In osteosarcoma, TMEM147 expression was negatively correlated with patient prognosis [20]. Several studies have shown that the function of the endoplasmic reticulum is closely related to hepatocellular carcinoma, but TMEM147 has not been reported in hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 62%
“…It has been shown experimentally that TMEM147 has a broader effect on transmembrane proteins in the endoplasmic reticulum and nuclear envelope, and turns TMEM147 into many additional putative regulator processes and a potential therapeutic target for a range of diseases [34]. Although not all the functions of TMEM147 are understood, in the current literature it has been shown that TMEM147 plays an important role in colon cancer pathogenesis [19] and osteosarcoma prognosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Increased TMEM147 expression was reported in colon cancer and osteosarcoma as a potential prognostic factor 20,30 . Xiang Rui Li et al found TMEM147 was expressed in goat PBMC and could mediate cell proliferation, apoptosis, and secretion of cytokines 31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, its cancer‐involving roles have not received sufficient attention. Wei Xie et al constructed a prognostic model composed of six TMEM protein family genes for osteosarcoma patients, but TMEM147 as the least important variable in the LASSO equation presented no significant difference between the tumor and normal groups 30 . Zhi Chen et al confirmed the prognostic implication and altered expression of TMEM147 in colon cancer, but the interpretation of functional enrichment analyses remained speculative 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation